(1-w)(5w+3)=0

Simple and best practice solution for (1-w)(5w+3)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (1-w)(5w+3)=0 equation:


Simplifying
(1 + -1w)(5w + 3) = 0

Reorder the terms:
(1 + -1w)(3 + 5w) = 0

Multiply (1 + -1w) * (3 + 5w)
(1(3 + 5w) + -1w * (3 + 5w)) = 0
((3 * 1 + 5w * 1) + -1w * (3 + 5w)) = 0
((3 + 5w) + -1w * (3 + 5w)) = 0
(3 + 5w + (3 * -1w + 5w * -1w)) = 0
(3 + 5w + (-3w + -5w2)) = 0

Combine like terms: 5w + -3w = 2w
(3 + 2w + -5w2) = 0

Solving
3 + 2w + -5w2 = 0

Solving for variable 'w'.

Factor a trinomial.
(1 + -1w)(3 + 5w) = 0

Subproblem 1

Set the factor '(1 + -1w)' equal to zero and attempt to solve: Simplifying 1 + -1w = 0 Solving 1 + -1w = 0 Move all terms containing w to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1w = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1w = 0 + -1 -1w = 0 + -1 Combine like terms: 0 + -1 = -1 -1w = -1 Divide each side by '-1'. w = 1 Simplifying w = 1

Subproblem 2

Set the factor '(3 + 5w)' equal to zero and attempt to solve: Simplifying 3 + 5w = 0 Solving 3 + 5w = 0 Move all terms containing w to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 5w = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 5w = 0 + -3 5w = 0 + -3 Combine like terms: 0 + -3 = -3 5w = -3 Divide each side by '5'. w = -0.6 Simplifying w = -0.6

Solution

w = {1, -0.6}

See similar equations:

| -3(x^3)+23(x^2)+24x+52=0 | | 36+4y=-8y | | y^2+8y+16=16 | | 8+3(x-8)=4-6(x-1) | | 35-14x= | | t/5-4=16 | | f(x)=2e^6x | | 2*cosy-siny=0.5 | | 16y-3=48-y | | =4x-2(3x-5) | | 50-8x=30 | | 7x+11=3(x+4) | | (3x-1)(x+2)=(3x-1)(7x-10) | | 4+55x=44x+5 | | 2d+4=18 | | x-8/x=5/7 | | 2x/12=4/5 | | x/12=6/8 | | 5log(2x+8)=2 | | 8y+6y+9p= | | 3log(x+6)=2 | | 2(5x+1)-3(2x-2)=28 | | 2-17/32 | | a+3-(a-3)= | | 96-7x=20x+18 | | 28/3(3^x) | | (x+3)(x-7)=(x+7)(x-3) | | y-6.5(y)=400 | | 8(x+3)=-3(x-2) | | 4x+4=7(x+2) | | 3x-9=9*3 | | (x+5)(x-9)=(x-4)(x-3) |

Equations solver categories